+0  
 
0
95
1
avatar

(3+5^2-8)4

 Dec 14, 2020

Best Answer 

 #1
avatar+156 
+1

(3 + 5^2 -8)4

 

I'm assuming you mean \((3 + 5^2 -8)^4\), but I'll solve it both ways.

 

\((3 + 5^2 -8)^4 = (3+25-8)^4 = 20^4 = 160,000\)

 

Or, if you meant \(4(3 + 5^2 -8)\), then \(4(3 + 5^2 -8) = 4(3 + 25 -8) = 4(20) = 80\)

 

I hope this helped. :)

 Dec 14, 2020
 #1
avatar+156 
+1
Best Answer

(3 + 5^2 -8)4

 

I'm assuming you mean \((3 + 5^2 -8)^4\), but I'll solve it both ways.

 

\((3 + 5^2 -8)^4 = (3+25-8)^4 = 20^4 = 160,000\)

 

Or, if you meant \(4(3 + 5^2 -8)\), then \(4(3 + 5^2 -8) = 4(3 + 25 -8) = 4(20) = 80\)

 

I hope this helped. :)

Firebolt Dec 14, 2020

81 Online Users

avatar
avatar